Brecht visita Nossa Cidade, de Thornton Wilder: aproximações e distanciamentos - Wilson Pereira de Oliveira (2010)
The present research intends to investigate the creation of a scenic process in which there is the attempt to establish a dialog between the conceptions systematized by Bertolt Brecht and the dramatic work of Thornton Wilder. Based on that premise the mise en scène of the play Our Town was confronted theoretically and in practice with some aspects of the framework proposed by Brecht specially about the counterpoint between the dramatical form and the epic form of Wilder. Therefore some analogies and differences were observed between the dramatic and scenic propositions of those two pradigmatic playwrights of the epic theater.